Deciphering the role of myofibroblasts in microvascular invasion of hepatocellular carcinoma - Liu, Xiang; Pan, Jiangyang; Wang, Lijia; Xie, Qiao; Fan, Tianbo; Wang, Qi (Frontiers in Pharmacology, 2025)
BackgroundHepatocellular carcinoma (HCC) often exhibits microvascular invasion (MVI), a feature with unclear mechanisms. Therefore, it is crucial to resolve its related cellular populations and molecular networks using single-cell analysis.MethodsBoth single-cell RNA sequencing (scRNA-seq) and RNA-seq data for HCC were obtained from public databases. ScRNA-seq data were clustered and annotated using Seurat. DAVID, CellChat, and Monocle 2 were used for scRNA-seq functional enrichment analysis, intercellular communication analysis, and cell trajectory analysis, respectively. We further assessed key gene expression in HCC cell lines and examined their effects on cell functions using CCK-8, scratch, and transwell assays.ResultsThe HCC ecosystem comprising myofibroblasts (MFs), hepatocytes, proliferative hepatocytes, endothelial cells, dendritic cells, proliferative NK/T cells, plasma B cells, and macrophages was revealed. MFs showed the greatest difference between MVI-absent and MVI-present patients and were subdivided into five clusters. Key genes for angiogenesis are overexpressed in MF2 cells and enriched in the pathways of angiogenesis, cell migration, cell proliferation, and signal transduction. Pseudotime analysis revealed MF2 cells from MVI-present patients clustered at the terminal state and positively correlated with angiogenesis. CAMK2N1 in the markers of MF2 cells was significantly associated with advanced M stage and poor prognosis. Further cellular assays showed that CAMK2N1 expression was downregulated in HCC cells, and its knockdown increased the proliferation, migration, and invasion levels of cancer cells.ConclusionThis study highlighted the role and potential mechanism of MFs in promoting MVI formation and provides a potential marker for HCC prognosis among MF markers.